The Mechanism of Coronary Artery Calcification in Centrally Obese Non-Diabetic Men: Study on The Interaction of Leptin, Free Leptin Index, Adiponectin, hs-C Reactive Protein, Bone Morphogenetic Protein-2 and Matrix Gla Protein - Antonia Anna Lukito; Syakib Bakri; Peter Kabo; Andi Wijaya (Cell and BioPharmaceutical Institute, 2020)
Background: The calcium in the artery was thought to be the result of the imbalance or dysregulation of the promoter and inhibitor cytokines influenced by various subclinical and clinical conditions. This study aimed to investigate the interaction between central obesity, as an early subclinical condition, also known as a chronic low grade inflammation condition and coronary artery calcium (CAC) in non-diabetic population including the underlying pathomechanisms of a CAC in the early stage of atherosclerosis.Materials and Methods: This was a cross-sectional pathway analysis study enrolling 60 central obesity non-diabetic men that underwent coronary calcium score scan, anthropometrics and biomarker assays.Results: There was a positive correlation between increasing free leptin index/adiponectin (FLI/A) ratio and CAC (r=0.297; p<0.05). There was a positive correlation between increasing FLI/A ratio and plasma high sensitive C-reactive protein (hs-CRP) (r=0.318; p<0.05). Plasma hs-CRP and bone morphogenetic protein-2 (BMP-2)-matrix gla protein (MGP) dysregulation were positively correlated (r=0.221; p<0.05) after adjusted to risk factors including insulin resistance, hypertension, age, and dyslipidemia.Conclusion: The study found that one of the pathways involved in CAC in the centrally obese non-diabetic male is might be due to an increase of free leptin and decrease of adiponectin. The free leptin and adiponection ratio also increased hs-CRP, which partially correlated to the dysregulation of BMP-2 and MGP.Keywords: coronary artery calcification, central obesity, adipokines, bone regulator protein, pathomechanism